The folding properties of the Escherichia coli maltose-binding protein influence its interaction with SecB in vitro. - Weiss, J B (1990)
It has been proposed that the cytoplasmic SecB protein functions as a component of the Escherichia coli protein export machinery by serving as an antifolding factor that retards folding of the precursor maltose-binding protein (preMBP) into a translocation-incompetent form. In this study, it was found that SecB directly interacts with wild-type preMBP and various mutationally altered MBP species synthesized in vitro to form a SecB-MBP complex that can be precipitated with anti-SecB serum. The association of SecB with wild-type preMBP was relatively unstable; such a complex was formed only when SecB was present cotranslationally or after denaturation of previously synthesized preMBP and was detected with only low efficiency. In marked contrast, MBP species that were defective in the ability to assume the stable conformation of wild-type preMBP or that exhibited significantly slower folding kinetics formed much more stable complexes with SecB. In one case, we demonstrated that SecB did not need to be present cotranslationally for complex formation to occur. Formation of a complex between SecB and MBP was clearly not dependent on the MBP signal peptide. However, we were unable to detect complex formation between SecB and MBP lacking virtually the entire signal peptide but having a completely intact mature moiety. This MBP species folded at a rate considerably faster than that of wild-type preMBP. The propensity of this mutant protein to assume the native conformation of mature MBP apparently precludes a stable association with SecB, whereas an MBP species lacking a signal peptide but exhibiting altered folding properties did form a complex with SecB that could be precipitated with anti-SecB serum.